(untitled) (Journal of Hama University, 2022)
The aim of this study was was to evaluate the effect of Chitosan dental dressing on Post-Operative Complications Following Surgical Extraction of impacted Mandibular Third Molars as pain, edema, and trismus. This clinical study was carried at oral and maxillofacial surgery department at Hama university. This study included random sample of 40 cases of impacted lower third molars on 20 patients. The ages of patients were between 18-30 years. The sample was divided into two groups: First group (study group): 20 impacted lower third molars was surgically extracted. Chitosan dental dressing was applied in alveolar cavity. Second group (controlled group): 20 impacted lower third molars was surgically extracted. It wasn’t applied anything in alveolar cavity. The study showed that Chitosan dental dressing have a positive effect on controlling pain, edema, and trismus after surgical extraction at first, second, third, seventh, tenth days.